MENINGKATKAN PRESTASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY - Sutrisno Sutrisno (Universitas PGRI Yogyakarta, 2016)
This research aims to improve student achievement by using model Course Review Horay the third grade students of SD Negeri 4 Ngraho in the academic year 2015/2016. This type of research is a classroom action research (PTK) is done through planning, action, observation, and reflection. The subjects were students of class III Elementary School 4 Ngraho in the academic year 2015/2016 which amounted to 17 students consisting of 9 students male and 8 female students. Class Action Research was conducted in two cycles. The data was obtained darihasil observation activities of teachers and students as well as the test results of the evaluation of student learning. Data were analyzed descriptively by using the average and the percentage of completeness students. Results of Class Action Research on learning using learning model Horay Course Review, showed that the average value of the results of the evaluation of student learning increased from 66.86 in pre-cycle into 78.43 in the first cycle and 85.86 in the second cycle. The percentage of completeness of evaluation of student learning outcomes increased from 40% in pre-cycle to 60% in the first cycle and 90% in the second cycle. In addition to the results of the evaluation study, student activities also increased from 49.70% in the first cycle to 74.69% in the second cycle. It is proved that the learning model Horay Course Review can improve learning achievement in third grade primary school students 4 Ngraho in the academic year 2015/2016.